Concurrent product-process-supply chain strategy formulation for small medium enterprises - Trapsilawati, Fitri; Subagyo, Subagyo; Firmansyah, Dimas Ardy; Masruroh, Nur Aini; Dharma, I Gusti Bagus Budi; Wibowo, Budhi Sholeh (SAGE, 2022)
Small-medium enterprises (SMEs) have the potentials to translate ideas into innovative products in a quick and efficient manner. Therefore, they should be supported to transform into well-established companies. However, SMEs often lack knowledge regarding operation and management. This study proposes three-dimensional concurrent engineering (3DCE) approach to help SMEs accelerate their growth through differentiation and efficiency, leading to high-quality yet low-cost products with efficient delivery. This study aimed to develop a strategic formulation framework incorporating the 3DCE concept in product functionality, concurrent process design, and appropriate supply chain solutions. The framework has been developed and implemented in food and beverage SME. Strategy development follows the traditional approach, including environmental analysis, strategy formulation, and strategy mapping. However, the result of environmental analysis extracted in the form of SWOT and Grand Strategy matrices are specifically piled into concurrent strategic theme covering the concurrent product, process, and supply chain aspects. Predominantly, product features covering the product innovation and functionality and process features covering segmentation-based and cross-functional process designs were tailored with innovative supply chain solutions based on the segmented model. The detailed framework and its implementation are highlighted accordingly.